2015
DOI: 10.1590/s0080-623420150000200009
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of caregivers for patients of cerebrovascular accidents: association of (socio-demographic) characteristics and burden

Abstract: Objective:Investigating the association between quality of life with socio-demographic characteristics and the burden of caregivers for individuals with cerebrovascular accident sequelae. Method: A descriptive, cross-sectional study with a sample composed of 136 caregivers. For data collection, a semi-structured questionnaire, the Barthel, Burden Interview and Short-Form-36 scales were used. Correlation analysis, t-Student test and F-test were used for the analysis in order to compare averages. Results: Signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
21

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 21 publications
1
30
0
21
Order By: Relevance
“…According to this same study, low back pain was one of the most common health‐related problems reported by caregivers. This is partly because of work overload, which can negatively impact on quality of life, with a negative correlation between pain and quality of life . In the present study, we did not evaluate pain.…”
Section: Discussionmentioning
confidence: 77%
“…According to this same study, low back pain was one of the most common health‐related problems reported by caregivers. This is partly because of work overload, which can negatively impact on quality of life, with a negative correlation between pain and quality of life . In the present study, we did not evaluate pain.…”
Section: Discussionmentioning
confidence: 77%
“…They appear to use various strategies of adaptation to the illness and treatment, such as performing household chores on the eve of chemotherapy sessions, or requesting work leave by citing other reasons for going to the hospital. Support may be incipient or even ambivalent, depending on individuals' clinical conditions, and their family dynamics, which can make the family a source of support or stress (19)(20) . Throughout results, before the intervention, the profile of interviewed women showed the axis of emotional social support was affected, there were negative responses involving aspects about how they felt or the emotional support received, like to feel valued, support to talk, social integration, among others.…”
Section: Discussionmentioning
confidence: 99%
“…After the intervention (motivational interviewing), there was a significant increase of satisfactory answers, demonstrating its effectiveness for the change of support behavior. Therefore, the increase of satisfactory answers is associated with psychological resources obtained in the coexistence with social networks, that is, the amount of emotional support received in the scope of family and work (19) . The importance of caregivers as disseminators of information and support behaviors is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family members in this situation suddenly find themselves without previous training [15, 17, 18]. This context contributes to the high level of caregiver burden [3], also influencing the worsening of their QofL [19]. Furthermore, without guidance, care for the aged cannot be expected to be understood and performed correctly by the caregiver [20], contributing to the consequent hospital readmissions of the older adults and the complications of negligent home care [21].…”
Section: Introductionmentioning
confidence: 99%